Recent results from the in situ study of hydrothermal crystallisations using time-resolved X-ray and neutron diffraction methods. - Walton, R; Norquist, A; Smith, R; O'Hare, D (2003)
We present new time-resolved powder diffraction data measured in situ during the hydrothermal crystallisation of two families of crystalline inorganic materials. In the first study, we have used time-resolved energy-dispersive X-ray diffraction (EDXRD) to follow the formation of zeolitic zinc phosphates from amine phosphates and zinc oxide in acidic solutions at 60-150 degrees C. The advantage of this method is the ability to penetrate a laboratory-sized reaction vessel and to measure data in short (< 1 min) time intervals. Integration of the Bragg peak intensities during the crystallisation of the product allows accurate crystallisation curves to be produced. In addition, in a number of cases, we observe the formation of transient crystalline intermediate phases which can be identified by use of a new three-element detector that allows a large amount of diffraction data to be measured during the experiment. We are thus able to show that three-dimensional zinc phosphate architectures often form via low-dimensional chain and layered phases, which is consistent with a recent aufbau model proposed for their formation. In the second study, we focus on the hydrothermal formation of ferroelectric barium titanate from TiO2 and barium salts in alkaline solution using time-resolved neutron diffraction. Although the time resolution of the neutron diffraction experiment is lower than the EDXRD experiment (data are measured in intervals of 5 min), we are able to penetrate reaction mixtures that are highly absorbing towards X-rays, and thus can measure data in a large volume reaction cell. Neutron diffraction data were collected on one of the highest-flux/highest detector-coverage diffractometers currently available; the GEM diffractometer at ISIS, UK. These experiments reveal that BaTiO3 crystallises after a large amount of TiO2 has been consumed; this implies that a dissolution crystallisation mechanism predominates. Additional mechanistic information is inferred by the observation of transient crystalline phases under certain reaction conditions.